The GL (1 | 1)-symplectic fermion correspondence - Creutzig, Thomas; Rønne, Peter B. (Nuclear Physics B, 2009)
In this note we prove a correspondence between the Wess-Zumino-Novikov-Witten model of the Lie supergroup GL (1 | 1) and a free model consisting of two scalars and a pair of symplectic fermions. This model was discussed earlier by LeClair. Vertex operators for the symplectic fermions include twist fields, and correlation functions of GL (1 | 1) agree with the known results for the scalars and symplectic fermions. We perform a detailed study of boundary states for symplectic fermions and apply them to branes in GL (1 | 1). This allows us to compute new amplitudes of strings stretching between branes of different types and confirming Cardy's condition. © 2009 Elsevier B.V. All rights reserved.
CRIS-Team Scopus Importer:2024-06-24